SIKAP DOSEN TERHADAP PEMBELAJARAN INTERPROFESIONAL EDUCATION (IPE) STUDI PADA DOSEN DI STIKES JENDERAL ACHMAD YANI YOGYAKARTA - Syahrani Hajri, Waode; Hutasoit, Masta; Nirmala Santiasari, Retty (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Application of IPE in academics prioritizes collaborative competencies to make students able to understand how to work interprofessionally, so as to foster readiness. Lecturer attitudes are considered as an important component in implementing successful IPE in academic environment. Objective: The purpose of this study was to examine and analyse lecturers attitudes towards interprofessional education. Method: This was descriptive comparative study with cross sectional design. Sampel were 31 lecturers from departments of nursing, midwifery, and medical record taken by purposive sampling. Modified questioner of Attitudes Toward Interprofessional Health Care Teams (ATHCT), Readiness for Interprofessional Learning Scale (RIPLS), and Attitudes Towards Interprofessional Learning in Academic Setting (ATILAS) were applied to examine lecturers attitudes. Result: The results indicate lecturer's positive attitude toward IPE, with an average score of statement item M = 3.96 on the attitude aspect to the interprofessional health care teams; M = 4.11 on attitude aspect to interprofessional education; as well as on attitudes towards interprofessional learning in academic setting with M = 3,93. Discipline, gender, and teaching experience have no significant relationship with overall attitudinal responses towards IPE. Conclusions: These findings can be used as a consideration of the intitution in applying Interprofessional Education at the academic settings. Keywords: Attitudes, Interprofessional Education, Lecturers